Da proporcionalidade à razoabilidade: entre a técnica e o princípio - Khamis, Renato Braz Mehanna (2014)
The present study aims to verify the legal status of proportionality and reasonableness, aiming to clarify whether they are legal rules or not and, if so, what species. Moreover, when we check their legal natures, we will be able to clarify if they are the same thing with different names, or if indeed we are facing separate legal institutes